Medical-health civil liability: Main challenges around the lex artis during the Covid-19 pandemic in Peru - Barco Hidalgo, Gino Leonardo Miguel (2024)
One of the key topics of discussion during and after the pandemic caused by the appearance of covid-19 around the world is the civil liability generated by the actions of health professionals (considering the health structure) before unforeseeable emergency situations. Likewise, the Peruvian health system was forced to face various challenges, through tools such as the application of public policies and implementation of special regulations, which mostly had an impact on the determination of the responsibility of health professionals during the state of health emergency. In this sense, in this research work, civil medical-sanitary liability will be addressed, based on a study of the application of the lex artis according to the national legal system. To do this, it will start with a study of medical-health civil liability in Peru, detailing what types of obligations apply depending on the case and identifying the actors in the health system who can be accused. Secondly, the lex artis is presented as a parameter of diligence, for which a study of concepts is provided, and it is differentiated from linked notions such as the lex artis ad hoc. Finally, the main challenges that Peru faced during the covid-19 pandemic and their impact on the determination of civil medical-health responsibility were established.